Reform of Chinas energy institutions and policies : historical evolution and current challenges - Zhao, J (Energy Technology Innovation Project, Kennedy School of Government, Harvard University, 2001)
China’s institutional settings and policies have played a crucial role in shaping China’s energy system. Drawing upon interviews and secondary source materials, this paper reviews the development of China’s energy institutions and policies over the past five decades and identifies factors that have influenced this development. This review shows a changing role of government in the energy sector—from complete control to decentralized control—with the government focusing increasingly on improving the effectiveness of regulatory oversight and less on the operational aspects of energy production. The commitment of the government to promote energy efficiency and the subsequent policies and programs have been and will continue to be important for improving the efficiency of energy use and restructuring the energy system. The key remaining issues are the optimal extent of government involvement and the most appropriate and effective means of intervention. This paper finds that Chinese institutions and policies have been very responsive to shortterm energy needs but do not necessarily support effective long-term strategies. Some institutional changes and policies displayed conflicting and perverse effects from a longterm perspective. Incremental adjustments in policy implementation during the transition from a planned economy to a market economy reduced the risk of serious mistakes in policy making and implementation, but distorted market signals in energy production, distribution, and utilization activities. The coordination issues among government agencies and between local and central governments in China have always been complicated and challenging, limiting the efficiency of policy implementation in China’s energy sector. Development, environment, and security concerns in the 1990s encouraged policies to promote cleaner and more efficient use of energy, with particular attention to the use of coal and the development of oil, natural gas, and electric power. This shift has led to a number of strategic changes and policies. However, a lack of detailed implementation rules and targets, an ineffective monitoring system, and a lack of proper regulatory or market-based policies to create a favorable condition for the commercialization of clean and efficient energy technologies have reduced the effectiveness of these policies.